Estrategia de mezcla de productos y performance de mercado de las librerías de Huamachuco, año 2016 - Acevedo Castillo, Juana Lidia (2016)
Thesis this work has been done in the city of Huamachuco, La Libertad, Peru. Its aim head m s that way support the Strategy Product Mix influences the Market Performance libraries Huamachuco, which has played a satisfaction. In reviewing the problematic reality, it has formulated the research question: How does Strategy Product Mix influences the Market Performance Libraries Huamachuco, 2015?. For data collection have been taken into account two populations: 11 workers and 942 client’s bookstores study; of them they have extracted samples of 11 workers and 87 clients respectively. They have been implemented customer surveys and workers have conducted interviews with representatives of bookstores. With the results obtained, and according to the scientific method has been carried out the analysis and discussion corresponding coming to demonstrate the validity of the hypothesis which states that : "The Strategy Product Mix, with the variety and level of updating their books and other articles directly influences the Market Performance libraries Huamachuco , 2015 " . Finally they formulated the conclusions and recommendations , the main conclusion that "indicators of both the independent variable and dependent on each qualify for (strengths ) and others below (weaknesses ) of its average for the sector; also according to their nature, they refer to a greater or lesser variety of products, as well as their level of renovation or innovation"; meanwhile the main recommendation stresses that "should make the extension of product lines , adding lines of other companies such as Agent of a Bank (BCP, Interbanc ), to recharge cell phones, etc.; and prior assessment should be discontinued lines or unprofitable or obsolete individual products".